(untitled) - Balassa, Bela A. (Washington, 1988)
Foreign economic relations and the situation of Japan in the world economy
Keywords: Foreign trade regulation,Quy tắc ngoại thương,Tiết kiệm và đầu tư,Saving and investment; Nhật Bản,Japan